IMPLEMENTASI ENGLISH ZONE (PENGGUNAAN BAHASA INGGRIS) DI POLITEKNIK NEGERI SRIWIJAYA - Ahmad Iman Mulyadi; Intan Putri; Hilda Puspita (Jurnal Ilmu Komunikasi Balayudha, 2022)
The English Zone can be translated as the English zone, which is a place in which there are a series of agendas, English learning media and rules that have been used to learn English. The rule made is that anyone who enters the English zone of the Politeknik Negeri Sriwijaya, students, employees, and the public are required to use English in communicating or speaking with students and lecturers of the English Department to serve visitors using English. Whoever violates the agreed rules, then he will be subject to sanctions or penalties. With this technique, students who enter their English zone must try as much as possible to communicate in English even with simple words or sentences. Politeknik Negeri Sriwijaya alumni are expected to be able to compete with alumni from all universities in Indonesia in all fields of work to be achieved. The research method used is a qualitative method with data collection techniques used, namely: interviews, observation and documentation.Based on the results of research that has been done regarding the implementation of the English zone (the use of English) at the Politeknik Negeri Sriwijaya. So it can be concluded that from the 6 (six) root causes (Manpower, Machines, Methods, Materials, Media, Motivation), the implementation activities of the English zone (the use of English) at the Politeknik Negeri Sriwijaya were carried out based on creative ideas, including: Making Regulations, Improvement of Facilities and Infrastructure, Socialization, Promotion.